Spontaneous complete remission in a child with acute lymphoblastic leukemia - Yetgin, Sevgi; Tuncer, A. Murat; Güler, Ertuğrul; Özbek, Namık (The Turkish Journal of Pediatrics, 1996)
A five-year-old girl was admitted to the hospital with fever and tender lymphadenopathy. She was diagnosed with acute lymphoblastic leukemia (ALL-L₃). Because of infection she was given antibiotics and a blood transfusion. Her bone marrow was in remission after 15 days without chemotherapy. This case emphasizes the role of transfusion and/or infection in obtaining complete remission without chemotherapy.
Keywords: leukemia; spontaneous complete remission; blood transfusion; infection